2019
DOI: 10.2478/amns.2019.1.00001
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic chaos in pendulum systems with delay

Abstract: Dynamic system "pendulum - source of limited excitation" with taking into account the various factors of delay is considered. Mathematical model of the system is a system of ordinary differential equations with delay. Three approaches are suggested that allow to reduce the mathematical model of the system to systems of differential equations, into which various factors of delay enter as some parameters. Genesis of deterministic chaos is studied in detail. Maps of dynamic regimes, phase-portraits of attractors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 1 publication
1
17
0
Order By: Relevance
“…One was the conventional ZMP trajectory and the other was the variable ZMP trajectory considering the environmental change, but all achieved stable walking. Figure 9(b), 3D simulation, shows that the CoM adjustment of the stabilization system achieves stable walking, which indicated that the walking pattern of biped robot was sensitive to the change of CoM trajectory [29][30][31][32]. Hence, predictive control can generate stable walking pattern by controlling the CoM motion, which is consistent with the real-time slight adjustment of CoG trajectory during human walking to adapt the change of road condition to achieve stable walking.…”
Section: Simulation Experiments and Analysissupporting
confidence: 55%
“…One was the conventional ZMP trajectory and the other was the variable ZMP trajectory considering the environmental change, but all achieved stable walking. Figure 9(b), 3D simulation, shows that the CoM adjustment of the stabilization system achieves stable walking, which indicated that the walking pattern of biped robot was sensitive to the change of CoM trajectory [29][30][31][32]. Hence, predictive control can generate stable walking pattern by controlling the CoM motion, which is consistent with the real-time slight adjustment of CoG trajectory during human walking to adapt the change of road condition to achieve stable walking.…”
Section: Simulation Experiments and Analysissupporting
confidence: 55%
“…By reasoning, whether the target is contained in the image and the target location is determined. By using the aforementioned method, the target recognition results with high accuracy are obtained [31][32][33][34][35][36][37].…”
Section: Experimental Conclusionmentioning
confidence: 99%
“…e singular study along with functional differential equations (FDEs) is considered very significant for the researcher's community, and the implementations of the FDEs have been noticed in the sixth decade of the nineteen century. e FDEs have a huge variety of applications in many fields; to mention few of them are, models of population growth [1], electrodynamics [2], infection models of HIV-1 [3], models of tumor growth [4], models based on chemical kinetics [5], B-virus infection hepatitis models [6], models of the gene regulations [7], and models of viral infections [8], and many more [9][10][11][12][13][14]. e singular study based on the differential models is very interesting, complicated, experimental, and challenging for the researchers due to the singularity appearance at origin.…”
Section: Introductionmentioning
confidence: 99%